The Peace-Education Curriculum Desirable for Pre- Primary and Primary Schools in Nigeria: A Religious Perspective - Fabarebo, Samuel I.; Sangotunde, Sunday O.; Ojetayo, Gabriel K. (European Scientific Journal, ESJ, 2019)
This paper focuses on re-appraising the peace-education curriculum already in use in primary schools in Nigeria. It also aims at re-wording the peace education curriculum suitable and relevant for pluralistic religious society and cultural diversity like the Nigerian nation. The research opines that peace-education is the process of acquiring values and knowledge and developing the right attitude, skills, and behaviours to live in harmony with one self, with others, and with the Nigerian multi-ethnicity compositions. The research dwells on the Content Analysis as a methodology for a systematic replicable technique for compressing many words of text into fewer content categories based on explicit rules of coding peace-education techniques desirable for a multi-cultural society like Nigeria. This methodology enables researchers to sift through large volumes of data with relative ease in a systematic fashion. It allows researchers to discover and describe the focus of individuals, groups, government institutions, and agencies or societal involvements in the formulation of peace-education desirable for Pre-primary and Primary education in Nigeria. The researchers also adopted the Critical Discourse Analysis (CDA) that stems from a critical theory of language which sees the use of language as a form of social practice. This will give rise to social practices that are tied to specific societal contexts which are considered as part of the existing social relations that could promote peace in the Nigerian society. The research recommends that right from the pre-primary and primary school levels of education, Nigerian children should be exposed to the spirit of oneness, unity in diversity, and social and religious values that promote peace and harmony. Also, a change of the present curriculum should be effected to reflect a pragmatic peace-education technique that is devoid of religious fanaticism, sectional polarization, cultural distortion, and ethnic parochialism. Its efficiency could only be determined if it is holistic in nature and garnished with sincere religious ingredients.